2013
DOI: 10.2139/ssrn.2280316
|View full text |Cite
|
Sign up to set email alerts
|

Money Growth and Infl‡ation: Evidence from a Markov Switching Bayesian VAR

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Similar evidence is documented by Canova and Menz () for Japan. Amisano and Colavecchio () investigate the nonlinearity in the pass‐through from money supply to inflation in a Bayesian Markov Switching framework for the U.S., the U.K., the Euro area and Japan over 1960–2012. They find evidence of a nonlinear relation between money growth and inflation.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Similar evidence is documented by Canova and Menz () for Japan. Amisano and Colavecchio () investigate the nonlinearity in the pass‐through from money supply to inflation in a Bayesian Markov Switching framework for the U.S., the U.K., the Euro area and Japan over 1960–2012. They find evidence of a nonlinear relation between money growth and inflation.…”
Section: Literaturementioning
confidence: 99%
“…Reasons for this are attributed to the loss of confidence during an economic downturn and downward price (Morgan, ). Evidence has shown that the adjustment of the price level to various macroeconomic variables, including inflation (Amisano and Colavecchioz, ), the exchange rate (Gervais and Khraief, ), changes in costs of firms (Peltzman, ; Taylor, ) is asymmetric. Prices may be rigid due to a number of factors which include: price leadership (Stigler, ); imperfect information (Stiglitz, ); imperfect competition (Kopecky and Van Hoose, ); menu costs (Barro, ); transaction costs (Obstfeld and Taylor, ); differences in financial structure (Cecchetti, ); different monetary regimes (Amisano and Colavecchio, ); central bank intervention (Mark and Moh, ); the downward rigidity of prices (Morgan, ; Rhee and Rich, ; Karras and Stokes, ); a liquidity trap situation (Krugman et al, ); health of a country’s financial system (De Long and Summers, ; Cecchetti, ); and changes in business and consumer confidence over the business cycle (Morgan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amisano and Colavecchio (2013) estimate a Markov Switching vector autoregressive model for Japan and found evidence of three di¤erent regimes of in ‡ation, one of which displaying features and the time allocation consistent with the empirical evidence of Japanese de ‡ationary episodes.…”
mentioning
confidence: 56%
“…In the analysis we carry out here we calibrate the euro area Low in ‡ation state with parameter values that qualitatively correspond to the state-speci…c features of the parameters estimated for Japan in Amisano and Colavecchio (2013). 3 The same argument applies to the US case.…”
Section: Estimation Resultsmentioning
confidence: 99%